Epidemiology and Risk Factors for Bacteremia in 144 Consecutive Living-Donor Liver Transplant Recipients - Kim, Sang Il; Kim, Youn Jeong; Jun, Yoon Hee; Wie, Seong Heon; Kim, Yang Ree; Choi, Jong Young; Yoon, Seung Kyu; Moon, In Sung; Kim, Dong Goo; Lee, Myung Duk; Kang, Moon Won (Yonsei medical journal, 2009)
Bacteremia is a major infectious complication associated with mortality in liver transplant recipients. The causative organisms and clinical courses differ between medical centers due to variations in regional bacterial epidemiology and posttransplant care. Further, living donors in Korea contribute to 83% of liver transplants, and individualized data are required to improve survival rates. We retrospectively analyzed 104 subjects who had undergone living-donor liver transplant from 2005 to 2007. Among the 144 consecutive living-donor liver transplant recipients, 24% (34/144) developed bacteremia, 32% (46/144) developed non-bacteremic infections, and 44% (64/144) did not develop any infectious complications. Forty episodes of bacteremia occurred in 34 recipients. The major sources of bacteremia were intravascular catheter (30%; 12/40), biliary tract (30%; 12/40), and abdomen (22.5%; 9/40). Gram-positive cocci were more common (57.5%; 23/40) than Gram-negative rods (32.5 %; 13/40) and fungi (10%; 4/40). The data revealed that the following factors were significantly different between the bacteremia, non-bacteremic infection, and no infection groups: age (p = 0.024), posttransplant hemodialysis (p = 0.002), ICU stay (p = 0.012), posttransplant hospitalization (p < 0.0001), and duration of catheterization (p < 0.0001). The risk factors for bacteremia were older than 55 years (odds ratio, 6.1; p = 0.003), catheterization for more than 22 days (odds ratio, 4.0; p = 0.009), UNOS class IIA (odds ratio, 6.6; p = 0.039), and posttransplant hemodialysis (odds ratio, 23.1; p = 0.001). One-year survival rates in the bacteremic, non-bacteremic infection, and no infection groups were 73.2%, 91.3%, and 93.5%, respectively. Early catheter removal and preservation of renal function should focus for improving survival after transplant.